Efeito da suplementação de whey proteins e treinamento resistido de doze semanas sobre a função hepática em ratos wistar - OLIVEIRA, Milena Silva de (2021)
Introduction: resistance training associated with the consumption of supplements, mainly an increase in whey proteins as a key to the increase in skeletal muscle mass. The liver is one of the main metabolic organs of the body, being responsible for the storage of energetic, metabolic substrate. Objective: to evaluate the effects of resistance training and protection consumption isolated from whey (whey proteins) on liver function in wistar rats. Methodology: The academic study approved by the animal research ethics committee (CEUA), of the Federal University of Maranhão (UFMA), under the number 23115.001161 / 2017-85, a sample was found by wistar rats with an initial age of 80 days and body mass from 200 to 250 g. Temperature control between 20ºC to 26ºC, and alternating light / dark cycle of 12 hours. Eight groups of 10 wistar rats were obtained, being Control Group (C), Control Training Group (CT), Group Supplied with 2g / kg / day of Whey Proteins (S2) Group supplemented with 4g / kg / day of Whey Proteins (S4 )), group supplemented with 6g / kg / day of Whey Proteins (S6), resistance group and supplemented with 2g / kg / day of Whey Proteins (TS2), resistance group and supplemented with 4g / kg / day of Whey Proteins (TS4), resistance training group and supplemented with 6g / kg / day of Whey Proteins (TS6). The rats were supplemented via gavage. After 12 weeks, the biomarkers were formed: Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase, Glutamyl Transferase Range (GGT) and a histological analysis for Hepatic Wines Data evaluation will be carried out in Graphpad Prism version 8.02. Results: The results allowed us to conclude that the sedentary group had higher levels of hepatic markers compared to the other groups, however, in the histological analysis there was no lesion or damage to the hepatic cells in any group, in addition, there was no raised trend for the increase of the liver weight of the trained and supplemented group in relation to the sedentary group. Conclusion: the results obtained in this study demonstrated that supplementation and physical training do not influence liver damage when comparing trained and supplemented rats to the control group.